2012 IEEE International Conference on Robotics and Automation 2012
DOI: 10.1109/icra.2012.6224660
|View full text |Cite
|
Sign up to set email alerts
|

Accurate calibration of two wheel differential mobile robots by using experimental heading errors

Abstract: Odometry using wheel encoders provides fundamental pose estimates for wheeled mobile robots. Systematic errors of odometry can be reduced by the calibration of kinematic parameters. The UMBmark method is one of the widely used calibration schemes for two wheel differential mobile robot. In this paper, the accurate calibration scheme of kinematic parameters is proposed by extending the conventional UMBmark. The contributions of this paper can be summarized as two issues. The first contribution is to present new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…This advantage not only improves the flexibility of the robot greatly in order to achieve fast target tracking and obstacle avoidance but also provides more references for robot motion control methods [19]. Non-omnidirectional robots are widely used on robotics research, industrial and non-professional applications as presented in [17], [4], [9]. However, generally they require more complex maneuvers and path planning than omnidirectional bases, such as Fig.…”
Section: Differentiate Degrees Of Freedommentioning
confidence: 99%
See 1 more Smart Citation
“…This advantage not only improves the flexibility of the robot greatly in order to achieve fast target tracking and obstacle avoidance but also provides more references for robot motion control methods [19]. Non-omnidirectional robots are widely used on robotics research, industrial and non-professional applications as presented in [17], [4], [9]. However, generally they require more complex maneuvers and path planning than omnidirectional bases, such as Fig.…”
Section: Differentiate Degrees Of Freedommentioning
confidence: 99%
“…UMBmark [3] was developed as a procedure to reduce the odometry error in differential drive robots, measuring and compensating these errors through a calibration process. However, the methodology used to verify the performance of the robot is widely used by mobile robot researchers [19], [17], [4], [9], and is used in this research to verify the consistence of the kinematic equations.…”
Section: Umbmark Test Proceduresmentioning
confidence: 99%
“…The robot motion model f r can be obtained by substituting (4)-( 5) into (6). It can be observed that the for the two-wheel differential drive robot, the sensor motion model f (δ jk ) = ⊕f r (δ jk )⊕ is completely specified, but for the parameters p = ( , r).…”
Section: Related Workmentioning
confidence: 99%
“…For most wheeled robot configurations that comprise encoders and exteroceptive sensors, the calibration process entails learning a mathematical model that can be used to fuse odometry and sensor data. For instance, calibrating a robot with a two-wheel differential drive robot involves learning various intrinsic parameters, namely the wheel radii and the axle length, and the extrinsic parameters, namely the pose of the sensors [5][6][7][8]. More generally, however, when the motion model of the robot is unavailable, calibration involves learning the relationships that describe the sensor motion in vector of wheel angular velocities at time instant t Z(t)…”
Section: Introductionmentioning
confidence: 99%
“…Chong [16] 은 로봇의 주행 이전의 연구에서는 이륜차동구동형로봇에 대해 오차원 인간의 복합효과를 고려한 정밀한 오도메트리 보정기법 [17] 을 제안하고 적절한 주행시험경로 설계를 통한 보정성능 향상 [18] 을 보였다. 또한, 최종 방향각 오차를 이용하는 새로 운 오도메트리 보정기법 [19] 을 …”
Section: 오도메트리의 오차 원인은 크게 시스템적 오차와 비시unclassified